STRATEGI PENGASUH PONDOK PASANTREN DALAM UPAYA MENINGKATKAN PENDIDIKAN FORMAL DI PONDOK MODERN - Sartika, Thea; Saputri, Juriati; Ilmi, Syarif Fadillah (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
Islamic values are taught in Islamic boarding schools, ranging from fiqh, creed, tawhid, and other concepts. The overarching purpose of pesantren is to guide its students towards developing Islamic personality and becoming future scholars who will preach. To achieve this, administration is needed to make it easier. So that this journal can achieve goals, namely: 1) Describe the strategy of pasantren caregivers in modern cottages, 2) describe the implications of pasantren caregiver strategies, 3) describe formal education strategies in pasantren cottages, 4) describe the strategies of caregivers in fostering female students in pasantren huts. Among Islamic educational institutions, modern pesantren promote formal education and religious instruction. One of the crucial tasks to be accomplished is to formalize education in the context of pesantren, as we must strike a balance between secular and religious lessons in light of today's increasingly advanced developments